Calculation methods investigation, of some thermodynamic & volumetric properties, for some non-ideal fluids. - SEBA, Fatheddine; TAOUTI Mohammed Belkacem; BOUREZG Mohammed Tahar (Université Amar Telidji- Laghouat FACULTE : TECHNOLOGIE DEPARTEMENT : GÉNIE DES PROCÉDÉS, 2024)
This study investigated the effectiveness of cubic equations of state (EOS) models, in predicting the phase behavior of carbon dioxide and water compared to experimental data. The PR model exhibited the best overall performance for both fluids, especially in regions dominated by weaker intermolecular forces. However, its accuracy weakened near the critical point and in the supercritical phase for both CO2 and water. The complex hydrogen bonding in water presented a significant challenge for all cubic EOS models, with the PR model showing the least deviation compared to simpler models like van der Waals. The Corresponding States Principle (CSP) and acentric factor (ω) are critical in this context. CSP suggests substances at equal reduced states have corresponding properties. The acentric factor, indicating molecular shape and polarity, is higher for water than for CO2, reflecting water's complex hydrogen bonding. This high acentric factor makes it difficult for cubic EOS models to predict water's phase behavior accurately, particularly in the liquid phase. While the PR model is useful for CO2 in specific conditions, more sophisticated EOS models are needed for accurate predictions of water behavior. Future research should explore advanced EOS models for polar fluids.
Chemical Engineering